RANCANG BANGUN APLIKASI E-LEARNING UNTUK PEMBELAJARAN AGAMA ISLAM BERBASIS ANDROID (Studi Kasus MIN 6 Bandar Lampung) - Putri Dwi Cantika; Bambang Hermanto (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2018)
Islamic religious education is very important for human life, especially in achieving inner peace and mental health in general, Islam is the best life guidance, prevention of wrongdoing the most powerful, unmatched moral control. This system aims as an alternative media to facilitate children and teachers and parents who want to get information about Islamic learning materials for early childhood and elementary school children. In this research, E-Learning application for Islamic learning built based on android using Java programming language. The method used in this application is the Waterfall method, and is designed using Unified Modeling Language (UML). This application contains data of Islamic learning materials for children ages 3-11 years that can facilitate the user to understand and know the learning of Islam. The results of test data using Equivalence Partitioning testing, shows that the management rules (rule) system can run according to function and the system can provide information well. In addition, based on testing data, this application is the application of User Friendly variable category with an average value of 4.33 (very good).